Proceedings of the 6th Conference & Exposition on Petroleum Geophysics : "Kolkata 2006", 9-11 January, 2006, Science City, Kolkata - Society of Petroleum Geophysicists (India). Conference & Exposition on Petroleum Geophysics 2006 : Kolkata, India); Mehta, C. H.; Society of Petroleum Geophysicists (India) (Dehradun : Society of Petroleum Geophysicists, 2006)
Papers presented at the conference.
"Theme: Geophysics for mitigating exploration risks."
Includes bibliographical references and index.
Keywords: Prospecting -- India -- Geophysical methods -- Congresses; Petroleum -- Prospecting -- India -- Congresses; Seismic prospecting -- India -- Congresses